Effectivity Comparison of Ketamine and Morphine as Post-Operative Analgesic in Spinal Surgery - Nenden Suliadiana Fajarini; Nancy Margarita Rehatta; Arie Utariani (Faculty of Medicine-Universitas Airlangga, 2019)
Introduction: Patients who undergo spinal procedure, experience the post-operative pain as the major problem. From the Visual Analog Scale (VAS), patients scale their pain around 8. An inadequate pain management could fasten the healing process and reduce patient life quality. Opioid group as the gold standard still inflicts several problems, such as respiratory depression. Moreover, the combination NSAID and opioid which used to suppress the side effect, still burden the healthcare cost. In a research of analgesic, through the discovery of N-Methyl D Aspartate receptor, researchers found an explanation of the ketamine effect in relieve chronic and intense pain which safer and cheaper. Method and Material: This research using single blind randomized control trial. Comparing 0.25mg/kg ketamine IV followed by ketamine 0,1mg/kg/h for the intervention group and 0.02mg/kg/h of morphine for the control group to manage the first 24 hours pain sensation. If patient VAS was more than 4, patient would get additional 0.5mg/kg ketamine (intervention group) and 25Î¼g fentanyl (control group). Result and Discussion: From 17 patients each groups, the VAS values were better in control group rather than on intervention group. Low dose ketamine can't be compared with morphine to manage post spinal procedure pain. There were no hemodynamic changes, respiratory rate depression, loss of consciousness and hallucination, nystagmus, vomiting and hyper salivation. Even though 11.8% of the subject were nausea. The morphine group tends to experience hemodynamic changes and loss of consciousness in the first 12 hours but still within normal range. In the control group, 47.1 % patients were having nausea in the first hour, but only 17.6% of them who actually vomited. Conclusion: The analgesic effect of morphine is higher than ketamine, but the amount effect of ketamine is lower than morphine so that ketamine is more effective and safer given in the room.